2020
DOI: 10.1155/2020/8578172
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors for Hepatitis B Virus Infection in Adolescent Blood Donors within Selected Counties of Western Kenya

Abstract: Hepatitis B virus is a widespread public health menace approximated to have infected 257 million people chronically by 2015. Data on the prevalence of HBV is important in formulating public health policies on HBV control like safe blood transfusion. Adolescents aged 15 to 24 years, known to engage in risky activities associated with HBV spread, constitute major blood donors in Kenya. Notwithstanding current blood donation safety measures, HBV still remain hazardous transfusion-transmissible infections in donat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
2
11
1
Order By: Relevance
“…is finding is consistent with studies conducted in Ethiopia [43], Kenya [44], and Ghana [45]. e reason for this finding might be because that the crucial means of acquiring transfusion transmissible infections among voluntary blood donors in Africa is sexual activity, multiple partners being one of the main risk factors [46,47]. Advances in Public Health It was found that having a family history of hepatitis was significantly associated with HBV infection.…”
Section: Discussionsupporting
confidence: 84%
“…is finding is consistent with studies conducted in Ethiopia [43], Kenya [44], and Ghana [45]. e reason for this finding might be because that the crucial means of acquiring transfusion transmissible infections among voluntary blood donors in Africa is sexual activity, multiple partners being one of the main risk factors [46,47]. Advances in Public Health It was found that having a family history of hepatitis was significantly associated with HBV infection.…”
Section: Discussionsupporting
confidence: 84%
“…This is most likely because this study couldn’t recruit enough females although similar studies in Ghana have reported a high prevalence of HBV infections among the female gender [ 25 , 26 ]. In contrast, several other studies reported higher proportions of HBsAg positivity among male blood donors [ 16 , 19 , 27 , 28 ]. The likely reasons for the different results were the different designs and settings employed by the different studies.…”
Section: Discussionmentioning
confidence: 69%
“…The prevalence of HBV infections was approximately 9% which is higher than the prevalence reported among young adults (18–25 years) voluntary blood donors in the three Kenyan Counties of Siaya 4.4%, Homabay 3.4%, and Kisumu 2.6% [ 19 ]. However, the prevalence was lower than the study conducted in Nigeria among secondary students who had a prevalence of 18.4% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for study populations, 19 studies involved HIV-infected individuals ( 31 , 33 , 40 , 41 , 43 , 44 , 47 , 50 , 52 , 54 , 55 , 60 , 64 – 70 ), 14 in other high risk groups [4 in liver disease patients ( 23 , 35 , 39 , 77 ), 2 in drug users ( 46 , 57 ), 2 in MSM ( 74 , 76 ), 2 in healthcare/medical waste workers ( 53 , 59 ), 1 study each for STI clinic attendees ( 51 ), kidney disease patients ( 34 ), and febrile patients ( 49 ), and 1 study in a combination of five high risk groups ( 22 )]. As for the low-risk group, 10 studies were performed in blood donors ( 37 , 48 , 56 , 58 , 61 , 62 , 71 , 73 , 75 , 78 ), 2 in pregnant women ( 36 , 45 ), 2 in outpatients ( 32 , 63 ), and 3 in a community setting ( 38 , 42 , 72 ). In terms of regional distribution, Nairobi had the highest number of studies at 16 ( 31 , 33 , 35 , 37 , 39 , 40 , 42 , 45 , 47 , 51 , 59 , 61 , 66 , 67 , 76 , 77 ), followed by Rift Valley at 8 ( 22 ,...…”
Section: Resultsmentioning
confidence: 99%
“…As for the low-risk group, 10 studies were performed in blood donors ( 37 , 48 , 56 , 58 , 61 , 62 , 71 , 73 , 75 , 78 ), 2 in pregnant women ( 36 , 45 ), 2 in outpatients ( 32 , 63 ), and 3 in a community setting ( 38 , 42 , 72 ). In terms of regional distribution, Nairobi had the highest number of studies at 16 ( 31 , 33 , 35 , 37 , 39 , 40 , 42 , 45 , 47 , 51 , 59 , 61 , 66 , 67 , 76 , 77 ), followed by Rift Valley at 8 ( 22 , 38 , 44 , 50 , 52 , 58 , 63 , 78 ), Coast at 7 ( 41 , 43 , 46 , 49 , 55 , 68 , 74 ), Nyanza at 6 ( 56 , 62 , 64 , 70 , 75 , 77 ), Central 3 ( 32 , 69 , 73 ), and the Eastern region at 1 study ( 53 ). No study was reported from the North Eastern and Western regions and one study did not specify the location ( 71 ), whereas 8 studies were multi-regional or nationwide ( 23 , 36 , 48 , 54 , 57 ,...…”
Section: Resultsmentioning
confidence: 99%